Tomie dePaola's Mother Goose favorites. - DePaola, Tomie, 1934- (New York : Grosset & Dunlop, 2000)
An illustrated collection of Mother Goose nursery rhymes, including well-known ones such as "Little Boy Blue" and less familiar ones such as "Six little mice sat down to spin.".
"First published in 'Tomie dePaola's Mother Goose' in 1985 by G.P. Putnam's and Sons.".
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
Wilson's Children.
3.5.
3.5
Keywords: Children's poetry; Nursery rhymes; Nursery rhymes; Nursery rhymes